Energy Offset Between Silicon Quantum Structures: Interface Impact of Embedding Dielectrics as Doping Alternative. Issue 9 (11th November 2014) - König, Dirk; Hiller, Daniel; Gutsch, Sebastian; Zacharias, Margit
<x xml:space="preserve">Abstract</x> Ultrasmall silicon (Si) nanoelectronic devices require an energy shift of electronic states for n‐ and p‐conductivity. Nanocrystal self‐purification and out‐diffusion in field effect transistors cause doping to fail. Here, it is shown that silicon dioxide (SiO2) and silicon nitride (Si3N4) create energy offsets of electronic states in embedded Si quantum dots (QDs) in analogy to doping. Density functional theory (DFT), interface charge transfer (ICT), and experimental verifications arrive at the same size of QDs below which the dielectric dominates their electronic properties. Large positive energy offsets of electronic states and an energy gap increase exist for Si QDs in Si3N4 versus SiO2. Using DFT results, the SiO2/QD interface coverage is estimated with nitrogen (N) to be 0.1 to 0.5 monolayers (ML) for samples annealed in N2 versus argon (Ar). The interface impact is described as nanoscopic field effect and propose the energy offset as robust and controllable alternative to impurity doping of Si nanostructures.